Pre-Operative Prediction of Mediastinal Node Metastasis Using Radiomics Model Based on 18F-FDG PET/CT of the Primary Tumor in Non-Small Cell Lung Cancer Patients - Zheng, Kai; Wang, Xinrong; Jiang, Chengzhi; Tang, Yongxiang; Fang, Zhihui; Hou, Jiale; Zhu, Zehua; Hu, Shuo (Frontiers in Medicine, 2021)
Purpose: The present study aimed to investigate whether a fluorine-18-fluorodeoxy glucose positron emission tomography/ computed tomography (18F-FDG PET/CT) -based radiomics model could predict pathological mediastinal lymph node staging (pN staging) in non-small cell lung cancer (NSCLC) patients undergoing surgery. Methods: A total of 716 patients with a clinicopathologically diagnosis of NSCLC were included in this retrospective study. The prediction model was developed in a training cohort that consisted of 501 patients. Radiomics features were extracted from 18F-FDG PET/CT of primary tumor. Support vector machine and extremely random trees were used for radiomics model building. Internal validation was assessed. An independent testing cohort contained other 215 patients. The performance of radiomics model (RM) and clinical node staging (cN staging) in predicting pathological node staging (pN0 vs. pN1&2) were compared for each cohort. The area under the curve (AUC) of the receiver operating characteristic (ROC) curve was applied to assess the model’s performance. Results: The AUC of the RM [0.81 (95% CI, 0.771~0.848); sensitivity, 0.794; specificity, 0.704] for the predictive performance of pN1&2 was significantly better than that of cN in the training cohort [0.685 (95% CI, 0.644– 0.728); sensitivity, 0.804; specificity, 0.568], (P value=8.29e-07, as assessed by Delong test). In the testing cohort , the AUC of the RM [0.766 (95% CI, 0.702~0.830); sensitivity, 0.688; specificity, 0.704] was also significantly higher than that of cN [0.685 (95% CI, 0.619– 0.747); sensitivity, 0.799; specificity, 0.568], (P value=0.0371, as assessed by Delong test). Conclusions: The RM based on 18F-FDG PET/CT was potential in mediastinal LN staging in patients with NSCLC.